2018
DOI: 10.1186/s12887-018-1089-8
|View full text |Cite
|
Sign up to set email alerts
|

A realist evaluation of a physical activity participation intervention for children and youth with disabilities: what works, for whom, in what circumstances, and how?

Abstract: BackgroundThe need to identify strategies that facilitate involvement in physical activity for children and youth with disabilities is recognised as an urgent priority. This study aimed to describe the association between context, mechanisms and outcome(s) of a participation-focused physical activity intervention to understand what works, in what conditions, and how.MethodsThis study was designed as a realist evaluation. Participant recruitment occurred through purposive and theoretical sampling of children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…The result regarding the factor fun was comparable to the results of Noonan et al (2016) who showed that 10–11-year-old primary school children indicated the factors fun, enjoyment, competence, and PA provision as important for their (out-of-school) PA participation [22]. The factors regarding playing together and motivation and stimulation from family or others were not found for children with asthma specifically, but they were found in children with a disability [23].…”
Section: Discussionsupporting
confidence: 77%
“…The result regarding the factor fun was comparable to the results of Noonan et al (2016) who showed that 10–11-year-old primary school children indicated the factors fun, enjoyment, competence, and PA provision as important for their (out-of-school) PA participation [22]. The factors regarding playing together and motivation and stimulation from family or others were not found for children with asthma specifically, but they were found in children with a disability [23].…”
Section: Discussionsupporting
confidence: 77%
“…The additional nine sources described more broadly how the F‐words facilitate the participation of children with disabilities in PA and rehabilitation. Four sources (Adolfsson, ; Mäkelä, ; Pickering, ; Willis et al, ) encouraged professionals working with children with disabilities to use the F‐words as motivators/incentives to engage children in PA programs and rehabilitation‐based interventions. Similarly, Adolfsson () and four other sources (Järvikoski, Martin, Autti‐Rämö, & Härkäpää, ; Jeglinsky, ; Lauruschkus, ; Lauruschkus, Nordmark, & Hallström, ) highlighted the importance of incorporating “fun” into medical rehabilitation to promote children's participation and engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Wright et al [27] call healthcare professionals the perhaps missing link to improve an active lifestyle and encourage behavioural change in individuals. Moreover, in recent years it has become more and more important to include the perspective of the children themselves [29][30][31][32][33][34][35]. This is especially stated in article 12 of the UN Convention of the Rights of the Child (UNCRC):…”
Section: Introductionmentioning
confidence: 99%